The Sustainable Environment in Uruguay: The Roles of Financial Development, Natural Resources, and Trade Globalization - Abraham Ayobamiji Awosusi (Frontiers in Environmental Science, 2022)
As the world continues to be a globalized society, there have been variations in environmental quality, but studies including trade globalization into the environmental policy framework remain inconclusive. Therefore, employing the time series dataset of Uruguay over the period between 1980 and 2018, the main objective of this current study is to investigate the effect of trade globalization, natural resources rents, economic growth, and financial development on carbon emissions. By employing the bounds testing procedures in combination with the critical approximation p-values of Kripfganz and Schneider (2018), the Autoregressive Distributed Lag estimator, and spectral causality test to achieve the goal of this research. The outcomes of the bounds test confirm a long-run connection between carbon emissions and these determinants. Moreover, from the outcome of the Autoregressive Distributed Lag estimator, we observed that trade liberalization is found to exert CO2 emissions in the long and short run. The economic expansion in Uruguay imposes significant pressure on the quality of the environment in the long and short run. The abundance of natural resources significantly increases environmental deterioration in the long and short run. Furthermore, we uncover that financial development does not impact environmental deterioration in Uruguay. Finally, the outcome of the spectral causality test detected that trade globalization, economic growth, and natural resources forecast carbon emissions with the exclusion of financial development. Based on the outcome, this study suggests that policies should be tailored towards international trade must be reassessed, and the restrictions placed on the exportation of polluting-intensive commodities must be reinforced.